(untitled) (Conference Zone, 2022)
Pregnancy is a time when many women experience physical discomfort like sore muscles, back pain, and pain in the breasts. Wearing the right clothes during this time is very important. Comfortable clothes can help reduce discomfort and make the overall experience of being pregnant easier to tolerate. Maternity clothes are functional clothes specially designed to take into account the anthropometric growth of the human body during pregnancy. These clothes are designed to have enough room in the waist to allow for maximum growth of the waist, and there is also width in the hips, bust and biceps, which is suitable for the growth of the human body during maternity. These clothes serve only in the second and third trimesters of pregnancy, i.e. 6 months.